Genetic Analysis Of Culm Strength And Its Related Traits In Rice (Oryza Sativa L.) (Applied Biological Research, 2019)
The present study was conducted on 48 rice genotypes with the aim to assess the genetic relationship between culm strength and its influencing traits in  rice. Culm strength of rice has been used as an index of lodging resistance  and it was measured as pushing resistance by prostrate tester. Correlation  analysis revealed that culm strength is significantly positively correlated  with culm diameter, panicle number and culm wall thickness. Principal  component analysis revealed that the first four principal components with  Eigen value > 1 explained 79.36% cumulative variance. The maximum  variation explained by culm strength and its related traits like culm  diameter and culm wall thickness which showed positive contribution in all  the four components. Distribution of genotypes into four clusters, based on  Ward’s minimum variance method, showed that cluster-IV had high mean  (261.4 g stem-1) and cluster-II low mean (96.21 g stem-1) values of culm  strength. The electron microscopic observations of vascular tissues of lower  most elongated internode of four genotypes ‘CR 401’ and ‘Pusa-44’ from  cluster-IV and ‘Swarna’ and ‘BPT-5204’ from cluster-II revealed  significant variation in vascular tissue and phloem diameter among the  tested genotypes. This indicated significant diversity among rice genotypes  which can be useful for identifying the QTLs for culm strength and for  releasing new cultivar.
Keywords: Cluster analysis; culm strength; principal component analysis; rice genotypes; vascular tissues